Political training as a pathway to power: The impact of participation in student union councils on candidate emergence - Martin Lundin; Oskar Nordström Skans; Pär Zetterberg (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2013)
We test the hypothesis that political training (experiences of debates, negotiations, coalition-building, etc.) in voluntary associations increases the probability of becoming a candidate in public elections. We apply a regression discontinuity design, comparing bare winners and bare losers in student union (SU) elections, to data on 5,000 SU candidates at Swedish universities (1982-2005). This data is linked to information on all candidates in Swedish public elections (1991-2010). As hypothesized, students who were elected to the SU council, and thereby received political training, were 34 percent (6 percentage points) more likely to run for public office than SU council candidates who did not win a seat. The analysis contributes to political recruitment literature by identifying arenas outside of representative democratic institutions that facilitate the step into election processes. It also provides evidence to an increasingly contested issue within political participation research by showing that activities in associations increase political involvement.
Keywords: D72; I20; 330; Political training; political recruitment; political participation; public elections; associations; regression discontinuity